Changes in the structure and propagation of the MJO with increasing CO2. (22nd May 2017) - Adames, Ángel F.; Kim, Daehyun; Sobel, Adam H.; Del Genio, Anthony; Wu, Jingbo
Abstract: Changes in the Madden‐Julian Oscillation (MJO) with increasing CO2 concentrations are examined using the Goddard Institute for Space Studies Global Climate Model (GCM). Four simulations performed with fixed CO2 concentrations of 0.5, 1, 2, and 4 times preindustrial levels using the GCM coupled with a mixed layer ocean model are analyzed in terms of the basic state, rainfall, moisture and zonal wind variability, and the structure and propagation of the MJO. The GCM simulates basic state changes associated with increasing CO2 that are consistent with results from earlier studies: column water vapor increases at ∼7.1% K −1, precipitation also increases but at a lower rate (∼3% K −1 ), and column relative humidity shows little change. Moisture and rainfall variability intensify with warming while zonal wind variability shows little change. Total moisture and rainfall variability increases at a rate this is similar to that of the mean state change. The intensification is faster in the MJO‐related anomalies than in the total anomalies, though the ratio of the MJO band variability to its westward counterpart increases at a much slower rate. On the basis of linear regression analysis and space‐time spectral analysis, it is found that the MJO exhibits faster eastward propagation, faster westward energy dispersion, a larger zonal scale, and deeper vertical structure in warmer climates. Plain Language Summary: Changes in the Madden‐Julian Oscillation (MJO) with increasing carbon dioxide (CO2 ) concentrations are examined using the Goddard Institute for Space Studies Global Climate Model (GCM). Four simulations performed with varying amounts of CO2 concentrations. We analyze the climatology and variability in rainfall and water vapor, and the structure and propagation of the MJO. The GCM simulates basic state changes associated with increasing CO2 that are consistent with results from earlier studies: column water vapor increases at ~7.1 % per degree warming, while precipitation also increases but at a lower rate, and column relative humidity shows little change. Moisture and rainfall variability intensify with warming. Total moisture and rainfall variability increases at a rate that is similar to that of the mean state change, and it is faster at the intraseasonal timescale. It is also found that the MJO exhibits faster eastward propagation, a larger zonal scale and deeper vertical structure in warmer climates. Key Points: MJO intensifies with warming, likely in association with changes in tropical rainfall variability The MJO exhibits faster eastward propagation with warming Zonal scale and depth of the MJO increase with warming